Concept of ethnic tourism (Journal of Geography and Environmental Management, 2018)
Various points of view of foreign scientists about the concept “ethnictourism” are presented in article,given the analysis of the terminologyexisting today. The clarified content of ethnic tourism and main varietiesof this type of tourism are singled out. On the basis of the review of theexisting definitionsthe author’s option of definition and classification ofethnic tourism is offered.